Deposition of mass-selected ions in neon matrices: CS2+ and C6 F6+: Low-Temperature Physics and Chemistry in Cryomatrice - Lorenz, Martin; Bondybey, Vladimir E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Infrared, visible absorption as well as laser induced fluorescence (LIF) and excitation spectra are obtained for several simple cations deposited from a mass selected ion beam. In the present preliminary study we demonstrate the successfull and clean mass selection by presenting spectra of samples obtained by depositing the isotopic 34S12C32S+ ion in natural isotopic abundance, and analysing its spectrum. Spectra of C6F6+ deposited from a 20 eV ion beam exhibit quite different inhomogeneous line profiles,suggesting that even the relatively low kinetic energy results in considerable damage of the solid. Analysis of the spectra indicates that the Jahn√Teller distorted vibrational structure in the doublydegenerate ground state of C6F6+ is strongly perturbed in the newly formed sites, which are presumably of lower symmetry. A 33√46 cm-1 splitting of the origin and other totally symmetric bands in emission is tentatively attributed to the spin-orbit splitting in the 2E1g ground state.